2017
DOI: 10.5455/ijlr.20170513100912
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Diagnosis in Graded Murrah Buffaloes Using Elisa Based Serum Progesterone Assay

Abstract: The present investigation was conducted to study the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Test accuracy on days 15, 16, and 17 outperformed those reported by Shah et al (2017), who obtained 80% accuracy of progesterone examination on days 37-40 post-insemination. Relatively similar accuracy was reported by Rashmi et al (2020), who found 80% accuracy of progesterone examination on day 20-24 postinsemination, and Srilatha et al (2017), who obtained 85% accuracy on day 21 post-insemination. In this study, progesterone measurement accelerated diagnosis time (Nyman et al 2018;Rashmi et al 2020).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Test accuracy on days 15, 16, and 17 outperformed those reported by Shah et al (2017), who obtained 80% accuracy of progesterone examination on days 37-40 post-insemination. Relatively similar accuracy was reported by Rashmi et al (2020), who found 80% accuracy of progesterone examination on day 20-24 postinsemination, and Srilatha et al (2017), who obtained 85% accuracy on day 21 post-insemination. In this study, progesterone measurement accelerated diagnosis time (Nyman et al 2018;Rashmi et al 2020).…”
Section: Resultssupporting
confidence: 81%
“…Until now, progesterone testing is considered the earliest method to diagnose pregnancy in cows. This method is 80% effective from day 21-24 post-insemination (Sah et al 2017;Srilatha et al 2017). Related research indicates examination time can be accelerated (Abdullah et al 2017;Siregar et al 2017;Srilatha et al 2017;Thasmi et al 2017;Widayati et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation